Konsep Relasi Dialogis Manusia dengan Tuhan Sebagai Upaya Mencari Manifestasi Someone to Talk dalam Perspektif Islam: Kajian Tafsir Ichwani terhadap QS. Al-Baqarah: 186 - S, Robi’atul Adawiyah; Ichwan, Moh. Nor (Lembaga Teewan Journal Solutions, 2026)
The growing prevalence of mental health problems, accompanied by increasing suicide rates linked to psychological instability, requires a multidisciplinary approach. This study aims to formulate a new interpretation of Qur'an Surah Al-Baqarah verse 186 using the IchwaniTafsir methodology as an integrative framework for understanding the dialogical relationship between human beings and Allah. The study employed a qualitative library research method by examining classical Qur'anic commentaries, academic books, scholarly journal articles, and official mental health reports. The findings reveal three interconnected dimensions of interpretation: a theological dimension emphasizing Allah's closeness to His servants, a psychological dimension highlighting spiritual intimacy as a source of emotional resilience, and a practical dimension positioning supplication as an accessible dialogical space for every individual. These findings demonstrate that Ichwani Tafsir provides a contextual perspective for integrating Qur'anic values with contemporary mental health issues.